2008
DOI: 10.1021/la8003855
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Gas Permeability of an Ionically Cross-Linked Langmuir–Blodgett Bilayer with a “Touch” of Salt

Abstract: The main barrier for gas permeation across ionically cross-linked Langmuir-Blodgett (LB) bilayers, made from a 5,11,17,23,29,35-hexakis[( N, N, N-trimethylamonium)-N-methyl-37,38,39,40,41,42-hexakis-n-hexamedecyloxy-calix[6]arene hexachloride (1) and poly(sodium 4-styrenesulfonate) (PSS), has been determined by measuring the effects of NaCl on the thickness of the PSS layer encased between the calixarene layers and the permeation characteristics of the resulting membrane. Specifically, the fact that NaCl incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…In previous work, we have shown that certain calix[6]arene-based LB films exhibit significant permeation selectivity toward He and N 2 , especially if they are “glued together” by cross-linking, e.g., when held together with polymeric counterions. We also found that gluing significantly enhances the robustness of these films . Figure shows a stylized illustration of a LB bilayer made from a porous surfactant containing multiple cationic sites, which has been glued together with polymeric anions.…”
Section: Introductionmentioning
confidence: 82%
“…In previous work, we have shown that certain calix[6]arene-based LB films exhibit significant permeation selectivity toward He and N 2 , especially if they are “glued together” by cross-linking, e.g., when held together with polymeric counterions. We also found that gluing significantly enhances the robustness of these films . Figure shows a stylized illustration of a LB bilayer made from a porous surfactant containing multiple cationic sites, which has been glued together with polymeric anions.…”
Section: Introductionmentioning
confidence: 82%
“…The results indicate that (i) the main pathway for permeation of the small He molecule is through the central pore of the calix [6]arenes, (ii) the main pathway for permeation of the larger CO 2 and N 2 molecules is through void spaces around the perimeter of the calix [6]arenes (due to dynamic gaps and/or physical defects), (iii) the combined cross-sectional area of the central pores of the calix [6]arenes is large relative to the dynamic gaps and/or physical defects around their perimeter, and (iv) ionic crosslinking of the amphiphile assembly reduces the number of dynamic gaps and physical defects that are present. 288 The gluing not only improves the quality and stability of the LB films but also their permselectivity characteristics for nanomembranebased applications. 289 The role of porous and nonporous amphiphiles and the effect of counterions on gluing and gas separation have been explored.…”
Section: Amphiphilic Assemblies For Novel Nanomembranesmentioning
confidence: 99%
“…S3 †). [29][30][31] The pure gases studied were He, N 2 and CO 2 . A membrane to be measured was placed in the permeation cell between two rubber O-rings with a support screen.…”
Section: Permeation Measurementsmentioning
confidence: 99%